Effect of earnings management on economic value added: A cross-country study - Zhen-Jia Liu (South African Journal of Business Management, 2016)
This paper addresses the association between earnings management and economic value added (EVA) among nations of the North American Free Trade Agreement (NAFTA), Association of Southeast Asian Nations (ASEAN), European Union (EU), and those classified as a newly industrialized country (NIC). Furthermore, an analysis of the earnings management behaviour is presented based on data from 2009 to 2013. The results indicated that a significantly inverse relationship exists between earnings management through either discretionary accruals (DAs) or real earnings management (REM) activities and EVA in NAFTA and EU nations. Moreover, a significantly positive relationship exists between earnings management through either DAs or REM and EVA in ASEAN and NIC nations. In addition, REM activities exhibit greater explanatory power among these nations.
Keywords: 650